The Effect of Family Administered Oxytocin Massage on Milk Flow in Breastfeeding Mothers for 0-6 Months - Rina Rina; Dini Fitri Damayanti; Wahyu Astuti (MEDICA (International Medical Scientific Journal), 2025)
Exclusive breastfeeding for infants aged 0–6 months is essential for optimal growth and development. One approach to support effective breastfeeding is the oxytocin massage technique, which provides psychological benefits such as relaxation, stress reduction, and increased maternal confidence and stimulates prolactin release, a hormone involved in breast milk production. This study aimed to analyze the effect of oxytocin massage performed by family members, supported by an instructional booklet, on breast milk production among breastfeeding mothers with infants aged 0–6 months in the working area of the Sungai Durian Community Health Center. This quantitative study used a pre-experimental one-group pretest–posttest design. A total of 37 respondents participated. Breast milk flow was assessed before and after the oxytocin massage intervention. Data were analyzed using the Wilcoxon test. The findings showed a significant improvement in breast milk flow following the intervention. Before the oxytocin massage, the mean breast milk flow score was 3.62 (range: 3–5), indicating poor milk flow. After the intervention, the mean score increased to 6.62 (range: 6–8), indicating good milk flow. The Wilcoxon test yielded a p-value of 0.000 (<0.05), demonstrating a statistically significant increase. In conclusion, oxytocin massage performed by family members using an instructional booklet significantly increases breast milk flow in mothers breastfeeding infants aged 0–6 months.